Multicentric variant of peripheral ossifying fibroma - Srikanth A Choudary; Archana R Naik; Madhukeshwara S Naik; D Anvitha (Wolters Kluwer Medknow Publications, 2014)
Peripheral ossifying fibroma (POF) is a solitary over growth of the gingiva known to arise from the cells of the periodontal ligament. The lesions usually start as a painless overgrowth of the interdental papilla unless associated with trauma and gradually involve the other counter parts of the gingiva. The lesion is more considered to be an inflammatory or reactive process rather than to be neoplastic. Here, the authors present a unique case of multiple POF in a young male adult aged 24 years where surgical excision was carried out quadrant wise. The biopsy specimen from multiple sites revealed similar histopathologic features consistent with POF, but also with the multicentric presentation of POF, which is a unique phenomenon. Multicentric variant of POF is indeed a rare case being only the second case so far which has been documented. Management of such case needs a multidisciplinary approach to prevent the recurrence along with regular long time follow-up.